Edukasi Kesopanan di Dunia Maya dan Dunia Nyata Pada Siswa SD Muhammadiyah 56 Jakarta Pusat - Suhendi, Sofyan Maulana; Seza, Taqy Putra; Pakerti, Ganesh; Harianja, Jordan Rafael (Jurnal Pustaka Dianmas, 2025)
The development of digital technology has significantly influenced interaction patterns among elementary school students, both in real-life and online environments. First-grade students are at an early stage of character formation, requiring appropriate guidance to understand politeness and communication ethics, particularly in the use of digital devices. This community service activity aimed to improve the understanding and polite behavior of first-grade students at Muhammadiyah 56 Elementary School, Central Jakarta, in both offline and online interactions. The activity employed an educative and participatory approach through observation, question-and-answer sessions, simple discussions, simulations, and pre-test and post-test assessments tailored to the students’ developmental characteristics. The results showed a notable improvement in students’ understanding of politeness in real-life and online contexts, as indicated by an increase in the average score from 4.9 in the pre-test to 7.2 in the post-test. In addition, students demonstrated positive behavioral changes, including the use of polite language, mutual respect, and early awareness of ethical behavior when using digital devices. This activity confirms that early education on politeness and digital ethics, delivered through contextual and continuous approaches, is effective in supporting character development among elementary school students.